2015
DOI: 10.1653/024.098.0414
|View full text |Cite
|
Sign up to set email alerts
|

The Red Imported Fire Ant (Hymenoptera: Formicidae) in the West Indies: Distribution of Natural Enemies and a Possible Test Bed for Release of Self-Sustaining Biocontrol Agents

Abstract: Sample collections of Solenopsis invicta Buren (Hymenoptera: Formicidae) were taken from 20 islands of the West Indies and evaluated for the presence of key pathogens and parasites of this invasive pest ant. We hypothesized that bottleneck events during the introduction of this ant species in the West Indies would have resulted in populations devoid, or nearly so, of natural enemies. Monogyne and polygyne social forms were found throughout the islands surveyed with monogyny being more prevalent (65%) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…), they then spread to China, Taiwan, Australia, and Mexico (Valles et al . ). The spread of red imported fire ants mostly occurs by export or import of merchandise from other countries (CABI ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…), they then spread to China, Taiwan, Australia, and Mexico (Valles et al . ). The spread of red imported fire ants mostly occurs by export or import of merchandise from other countries (CABI ).…”
Section: Introductionmentioning
confidence: 97%
“…Red imported fire ants originated in South America (Vinson & Sorenson 1986). After red imported fire ants were first introduced and became widespread in the southern part of the USA and Caribbean (Morrison et al 2004), they then spread to China, Taiwan, Australia, and Mexico (Valles et al 2015). The spread of red imported fire ants mostly occurs by export or import of merchandise from other countries (CABI 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other invasive species widely studied were S. invicta 1972 (Levia & Frost, 2004;Bertelsmeier et al, 2015;Sung et al, 2018) and A. gracilipes (Bertelsmeier & Courchamp, 2014;Bertelsmeier et al, 2015;Jung, et al, 2017). Native from South America (Vinson & Sorenson, 1986), S. invicta was first introduced and spread in the southern part of the USA and the Caribbean (Morrison et al, 2004), and then was dispersed throughout China, Taiwan, Australia, and Mexico (Valles et al, 2015). In addition, large areas in Mexico, northern South, and Central America, the Caribbean islands, part of the Mediterranean region, as well as some areas close to the Black and Caspian Seas, are at high risk of invasion by this ant (Morrison et al, 2004).…”
Section: Evaluation Of the Applicability Of Species Distribution Mode...mentioning
confidence: 99%
“…B. bassiana alginate pellets, coated with peanut oil produced significant decrease in S. invicta population indices and could be recommended as control measurement in the field (Bextine & Thorvilson, 2002). A survey of the presence of key pathogens and parasites of S. invicta in the West Indies, undertaken by Valles et al (2015), revealed as the most promising pathogen the microsporidian Kneallhazia solenopsa; also, Vairimorpha invictae, was detected in St. Croix, as well as the Solenopsis invicta densovirus (SiDNV). Two species of Pseudacteon decapitating flies were found to have dispersed into the Bahamas.…”
Section: Control Eradicationmentioning
confidence: 99%